2020
DOI: 10.4235/agmr.19.0051
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of the Lawton Instrumental Activities of Daily Living Scale to Turkish: Validity and Reliability Study

Abstract: Functional capacity is a complex concept that includes basic activities of daily living (BADL), instrumental activities of daily living (IADL), 1) and advanced activities. 2) Since inadequacies in BADL affect daily activities, work performance, and leisure activities, BADL is one of the most important indicators of success to define the skill level, demonstrate the effectiveness of rehabilitation, and determine a person's ability to perform activities of daily living. 3,4) The BADL may decline due to age, a sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 28 publications
1
28
0
Order By: Relevance
“…In our study for criterion validity, the association between Lawton IADL with FAAM-ADL, SF36-PCS scores showed moderate correlations and strong correlation with ADL-Barthel, also a weaker correlation observed with SF36-MCS. Accordingly, the Turkish study observed IADL correlated to the independency level and basic ADL-Barthel and Katz as valid tools to apply in the elderly Turkish community (Isik et al, 2020).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In our study for criterion validity, the association between Lawton IADL with FAAM-ADL, SF36-PCS scores showed moderate correlations and strong correlation with ADL-Barthel, also a weaker correlation observed with SF36-MCS. Accordingly, the Turkish study observed IADL correlated to the independency level and basic ADL-Barthel and Katz as valid tools to apply in the elderly Turkish community (Isik et al, 2020).…”
Section: Discussionmentioning
confidence: 94%
“…The participating elderly in this study had a proportional cognitive level (AMT, 9.5 6 0.9). Isik et al expressed that low cognitive function could cause impairment in decision-making abilities that might have an effect on ethics relating to the study and informed consent, and affect IADL abilities (Isik et al, 2020). Therefore, we used AMT scores !8 as an inclusion criterion.…”
Section: Discussionmentioning
confidence: 99%
“…The functional status of the patients was assessed by the Katz Activity of Daily Living Scale (ADL) 16 and the Lawton-Brody Instrumental Activities of Daily Living Scale (IADL), 17 and cognitive status was assessed by the Mini-Mental State Examination (MMSE). 18 In the first interview, after collecting demographic data of the patients and their caregivers, the Morisky Green Levine Adherence Scale (MGLS) was applied to the patients who used the medications themselves, and to the caregivers for the others, and the adherence of patients with dementia treatment was evaluated.…”
Section: Methodsmentioning
confidence: 99%
“…Although the highness of the HS-EAST score indicates a potential increase in the risk of elder abuse, a score of 3 or more can be interpreted as the presence of abuse (13). They all have Turkish validity and reliability studies and suitable for using in Turkish elderly population (13)(14)(15)(16)(17).…”
Section: Methodsmentioning
confidence: 99%